2016
DOI: 10.3233/jad-150952
|View full text |Cite
|
Sign up to set email alerts
|

Different Clinical and Neuroimaging Characteristics in Early Stage Parkinson’s Disease with Dementia and Dementia with Lewy Bodies

Abstract: Parkinson’s disease with dementia (PDD) and dementia with Lewy bodies (DLB) both commonly exhibit brain Lewy body pathology and similar end-stage symptoms, but early symptoms differ. To clarify these differences, we compared the demographic characteristics, symptoms, cognitive and affective functioning, activities of daily life, and neuroimaging results between PDD (n = 52) and DLB (n = 46) patients. In measures of cognitive functioning, PDD patients had worse Hasegawa dementia scale-revised (HDS-R) scores (11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
4
20
1
2
Order By: Relevance
“…4 The rate of postural hypotension in both case series is much lower than that reported in other literature on DLB patients, ie 50%. 22 The lower rates of postural hypotension may be related to under-recognition. Similar to our findings, in a study of 22 Chinese DLB patients (mean age, 74 ± 8 years; mean MMSE score, 16 ± 7; mean NPI score, 24 ± 16), three most commonly observed BPSDs were visual hallucinations (86%), delusions (64%), and anxiety (59%); total NPI score was an independent predictor of caregiver burden (odds ratio=1.537; P=0.048).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The rate of postural hypotension in both case series is much lower than that reported in other literature on DLB patients, ie 50%. 22 The lower rates of postural hypotension may be related to under-recognition. Similar to our findings, in a study of 22 Chinese DLB patients (mean age, 74 ± 8 years; mean MMSE score, 16 ± 7; mean NPI score, 24 ± 16), three most commonly observed BPSDs were visual hallucinations (86%), delusions (64%), and anxiety (59%); total NPI score was an independent predictor of caregiver burden (odds ratio=1.537; P=0.048).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, in a study of 22 Chinese DLB patients (mean age, 74 ± 8 years; mean MMSE score, 16 ± 7; mean NPI score, 24 ± 16), three most commonly observed BPSDs were visual hallucinations (86%), delusions (64%), and anxiety (59%); total NPI score was an independent predictor of caregiver burden (odds ratio=1.537; P=0.048). 22 Clinicians should pay particular attention to BPSD, particularly visual hallucinations and anxiety symptoms, when managing Chinese LBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…DLB patients can develop parkinsonism of increasing severity over the years with prevalence between 60 and 92% , although 18% of neuropathologically confirmed DLB cases never developed . Rest tremor is less frequent in DLB than PDD and in DLB is usually milder and more symmetrical . More severe parkinsonism is associated with PDD ; the PIGD phenotype is more likely to be found in PDD (88%) and DLB (69%) compared to PD (38%) .…”
Section: Methodsmentioning
confidence: 99%
“…Visual recognition memory, semantic fluency and ideomotor praxis are more severely impaired in DLB patients , who also show significantly lower scores on the tests of attention, executive function and constructional tasks . Episodic verbal memory is also worse in DLB than PDD, and the rate of cognitive decline is faster in DLB than PDD and AD . One study showed that the average annual decline in MMSE score in DLB is approximately two points in comparison with PDD (1.8) and AD (1.6) .…”
Section: Methodsmentioning
confidence: 99%
“…Ezek alapján úgy tűnik, hogy DLB esetében gyorsabb progresszió mutatkozik a kognitív tünetek szempontjából a PDD-hez képest [49], a kognitív diszfunkciók profiljá-ban pedig szintén eltérés tapasztalható, már korai fázis-ban, amennyiben a DLB-ben kifejezett a vizuospaciális orientáció zavara, ami mellett a végrehajtó funkciók zavara is súlyosabb károsodást mutat a PDD-hez és ADhez képest is [37]. A memóriakárosodást DLB-ben az AD-hez képest kisebb fokúnak, a PDD-hez képest súlyo-sabbnak mutatták ki a vizsgálatok a betegség korai szakaszában [50]. A pszichiátriai tünetek tekintetében mind a PDD-hez, mind az AD-hez képest gyakoribbak és súlyo-sabbak az affektív tünetek és a pszichotikus tünetek (kü-lönösen a vizuális és extracampin hallucinációk, tévesz-mék) [37].…”
Section: öSszefoglaló Közleményunclassified